Differential migration of the sexes of Pochard Aythya ferina: results from a European survey - Carbone, Chris; Owen, Myrfyn (Wildfowl, 1995)
The number of male Pochard per 100 females varied from 300 at 57 North to 75 at 37 North throughout its European and North African range. Sex ratio bias related to long term mean January temperatures was also found, but as temperature is correlated with latitude, these results cannot be used to reject any of three hypotheses (cold tolerance, breeding advantage and intersexual competition) put forward to explain differential migration. However, studies of breeding biology and habitat use of duck species offer greater support for the intersexual competition hypothesis. This survey indicated that the sex ratio in this species is male biased, and suggested that the overall sex ratio lies between 140 and 230 males per 100 females. As sex ratios are near unity at hatching, females must suffer significantly higher mortality at some stage during development or adulthood. It has been suggested that adult female mortality may be particularly high during autumn migration and the winter season (Owen & Dix 1986) and that this is likely to be responsible for the disparity. There may also be an effect of higher hunting pressure at the southern end of the range where females winter predominantly.